The concept of value co-creation : A critical literature review - Heino, Annika (fi=Turun yliopisto|en=University of Turku|, 2018)
Since the establishment of service-dominant logic in 2004 the concept of value co-creation has gained a lot of interest as well as critics among academic researchers. Most of the discussion revolves around the idea of co-creation and its philosophical underpinnings. The scholars have not reached mutual understanding about the concept of value co-creation and the interpretations and definitions of value co-creation vary greatly, which has led to theoretical dysfunctionalities and practical confusion. This thesis aims at defining the concept of value co-creation by the means of critical literature review. The study examines how the citations of value co-creation have developed over the period of 2004–2014, what are the key elements of the concept of value co-creation in the literature, and how the use of the concept of value co-creation varies among the articles. The theoretical framework discusses the key approaches that study value co-creation. In the light of the literature review an analytical framework for value co-creation is presented as a basis for examining the use of the concept of value co-creation in literature. The research was carried out as a critical literature review. 967 articles in total were selected for the study. In addition, content analysis was conducted to analyze, structure and condense the literature. As a result, the value co-creation content of the selected academic journals is presented quantitatively and analyzed critically. The findings reveal that value co-creation is largely discussed from various angles, but the definitions vary or are not featured at all. In addition, many articles only discuss value co-creation only at a superficial level. There is a lack of articles that focus on developing the concept and establishing the key elements of value co-creation. Service-dominant logic has had a large influence on the broad discussion on value co-creation, but the additional perspectives also engage into the development of the concept of value co-creation and shape its meaning. The findings of this study strengthen the presupposition that value co-creation is a weakly defined and ambiguously used term in academic literature. The findings are alarming, and it would be extremely necessary to establish a clear definition for value co-creation so the refinement of value co-creation and service-dominant logic could continue.